(3GdWYf HGdfbV aj GdehGO GdeOfjI hGdJLGQjI (B/s - (3WdHI, CfhQs ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2004)
(3Tcd GdWYf(B: (3LhGR GdWYf HGdfbV, bHhd GdWYf, fMVjQ GdWYf(B: (3bjO GdWYf hGYdGfg, ePcQGJ GdNUhe heSJfOGJge, GdGONGd hGdJONd aj GdWYf, ePcQI fjGHI GdWYf, GdMce aj GdWYf(B: (3GNWGQ GdNUhe HGdLdSI, fXQ GdWYf hGdMce ajg, GdfaV Gdcdj hGdLRFj ddMce GdeWYhf ajg, YOe LhGR GdWYf aj CMcGe GdfbV, GdeSJMOK ef GdeHGOF GdbGfhfjI GdJj bQQJgG eMceI GdfbV(B: (3QaY GdWYf HGdfbV, ejYGO GdWYf HGdfbV, GdNUhe aj GdWYf HGdfbV, CSHGH GdWYf HGdfbV, LhGR GdWYf HGdfbV, GdMce aj GdWYf HGdfbV, GdGNJUGU GdehVhYj deMceI GdfbV, GdfbV hGdGMGdI(B.s
(3GdeQGLY U(B. 1076s
Keywords: (3GdWYf aj GdCMcGe(B- (3eUQs; (3GdbGfhf GdJLGQj(B- (3eUQs; (3GdbGfhf GdeOfj(B- (3eUQs; (3fbV GdCMcGe(B- (3eUQs